Análise fractal em imagens radiológicas digitalizadas de osso de rato com osteoporose induzida por corticóides - Jamacarú, Valmirlan Fechine (2010)
Traditional methods for texture analysis are classified into two categories: geometry and statistics. This study allowed the quantification of bone loss in two anatomical sites in the rat femur, the distal third with morphological analysis and fractal measure and the third medium in which was measured radiographic bone density. The main objective was to calculate the fractal dimension (FD) of the complex trabecular bone in the scanned image of the rat femur, and evaluate the process of bone demineralization induced by corticosteroid for 28 days. The Wistar albino rats were divided into two groups of 32 animals: the control group and hydrocortisone (HYDRO). The rats in group HYDRO were subjected to corticosteroid daily, by intramuscular dose of 18 mg/kg/day for a period of 7, 14, 21 and 28 days. The control group was subjected to administration of saline, by the same via and for the same period. The animals were sacrificed 7, 14, 21 or 28 days of treatment, as its subgroups, the right and left femurs were dissected and cleaned. Then, the bone specimens were radiographed in the anteroposterior incidence with mammography unit using the standardized technique. The images of the bony region of interest were captured in a standardized manner using a surgical microscope equipped with a video camera. The program SAMOS performed the processing of images, getting the calculation of the number of bone trabeculae, the number of junctions, number of nodes and trabecular area. Then the skeletonized image was inserted into the program Image J determined that the fractal dimension. To obtain the radiographic optical density (DOR), the pieces were radiographed with an aluminum step that served as the reference optical density. The digital image was obtained with the program Digora, and the DOR measured at the middle third of the femur. Results: The number of trabeculae measured in the HYDRO group was significantly higher (P =0,0497) that observed in the control group only on day 28 for the right femur. On the left there is the same behavior ( P =0,0384). For the number of junctions in the HYDRO group was significantly higher (P =0,0498) that observed in control only on day 28 for the right femur; already left for the increase in group HYDRO was also significant (P =0,0440). For the number of nodes there was no statistically significant differences between groups at any time. In relation to the trabecular area, there was a significant decrease in right and left femurs in the HYDRO group, resulting to the right side (P=0,0408) and (P=0,0429) in days 21 and 28 respectively, and for the left (P=0,0401) and (P=0,0451) in days 21 and 28 respectively. The fractal values accused a significant increase in group HYDRO compared to control, with (P =0,0456) to the right femur and (P =0,0495) to the left, both observed only on day 28. As the DOR there was a significant reduction in the HYDRO group compared to control, with (P =0,0002) for the right limb on day 21, reduction also observed in the group HYDRO (P< 0,0001) on the 28th day. These data demonstrate that the system constitutes a method to quantify processes of change in trabecular pattern. Structural analysis of the bone, as well as calculating fractal found bone loss, a fact consolidated by the DOR.